DAMPAK PENERAPAN E-COMMERCE DAN MANAJEMEN KEUANGAN TERHADAP KINERJA KEUANGAN USAHA KECIL MENENGAH (UMKM) KOTA KUPANG - Moni Yuniati Siahaan; Wilhelmina Muni; Selfesina Samadara (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the effect of e-commerce adoption and financial management on the financial performance of Small and Medium Enterprises (SMEs) in Kupang City. Methods: The study employs a quantitative approach using a survey method through Likert-scale questionnaires distributed to 120 SME owners, selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 25, preceded by validity, reliability, and classical assumption tests.Results: The results show that partially, e-commerce has a positive and significant effect on financial performance (t = 5.432; p = 0.000), as does financial management (t = 3.876; p = 0.001). Simultaneously, both variables have a significant effect on financial performance (F = 45.210; p = 0.000). The coefficient of determination (R²) of 0.58 indicates that 58% of the variation in financial performance can be explained by these two variables.The findings indicate that e-commerce has a more dominant influence compared to financial management; however, both variables are complementary in improving SME financial performance. Therefore, the integration of business digitalization and sound financial management is a key factor in enhancing the competitiveness and sustainability of SMEs in Kupang City. Keywords: E-Commerce, Financial Management, Financial Performance, SMEs,